The House of Dust: A Symphony - Aiken, Conrad, 1889-1973 (Salt Lake City, UT : Project Gutenberg, 1998)
"The House of Dust: A Symphony" by Conrad Aiken is a poetic work structured in three parts, likely written in the early 20th century. This intricate piece weaves together themes of life, death, and the ephemeral nature of human experience, exploring the struggles of existence against the backdrop of a rich, symbolic cityscape. The text invites readers to contemplate dreams, aspirations, and the poignant illusions that shape our realities. The opening of the poem introduces a somber yet vivid atmosphere, where the transition from day to night is marked by a haunting beauty. A dreamer wanders through the city, observing the interplay of shadows and light as people move amidst the rain. The imagery evokes a sense of collective experience, encompassing themes of love, loss, and the inescapable passage of time. Characters emerge through their reflections and aspirations, creating a vivid tapestry of emotions that engage the reader's senses, while the overarching motif of a city in flux serves as a poignant reminder of the impermanence inherent in both life and dreams. (This is an automatically generated summary.)
Release date is 1998-03-01
Produced by Judy Boss, and David Widger
Keywords: American poetry; Pastoral poetry